2007
DOI: 10.1073/pnas.0609737104
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized messenger RNA induces translation errors

Abstract: To investigate the effect of RNA oxidation on normal cellular functions, we studied the translation of nonoxidized and oxidized luciferase mRNA in both rabbit reticulocyte lysate and human HEK293 cells. When HEK293 cells transfected with nonoxidized mRNA encoding the firefly luciferase protein were cultured in the presence of paraquat, there was a paraquat concentration-dependent increase in the formation of luciferase short polypeptides (SPs) concomitant with an increase in 8-oxoguanosine. Short polypeptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
173
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(180 citation statements)
references
References 14 publications
4
173
0
3
Order By: Relevance
“…13 Messenger RNA oxidation is associated with a decreased translation efficacy even in intact ribosomes and the production of defective proteins caused by impaired translation fidelity. 16,35 Oxidation of astroglial GLAST mRNA by ammonia (Figs. 4, 8) may explain in part the known decrease of GLAST expression and glutamate uptake in cultured astrocytes, 36 which contributes to ammonia-induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…13 Messenger RNA oxidation is associated with a decreased translation efficacy even in intact ribosomes and the production of defective proteins caused by impaired translation fidelity. 16,35 Oxidation of astroglial GLAST mRNA by ammonia (Figs. 4, 8) may explain in part the known decrease of GLAST expression and glutamate uptake in cultured astrocytes, 36 which contributes to ammonia-induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized mRNAs lead to loss of normal protein level and protein function and potentially produce defective proteins leading to protein aggregation, a common feature of neurodegenerative diseases [150]. Recently it has been shown that the translation of oxidized mRNA in cell lines causes the accumulation of short polypeptides, which is a result of premature termination of the translation process of the oxidized mRNA and/ or the proteolytic degradation of the modified protein containing the translation errors due to the oxidized mRNA [151]. Additionally, it has also been shown that the oxidative damage to E. coli 16S rRNA results in the formation of short complementary DNA (cDNA) [152].…”
Section: Rna Oxidation and Repairmentioning
confidence: 99%
“…While oxidative damage to DNA is essentially repaired through the base excision repair (BER) pathway, no evidences of similar repair processes have been described for RNA molecules, even though some BER proteins recently entered the arena of the RNome world (138). If not repaired, damage to RNA molecules may lead to ribosomal dysfunctions and erroneous translation; thus, significantly affecting the overall protein synthesis mechanism (38,135). Moreover, RNA damage has been shown to cause cell cycle arrest and cell death with or without the contribution of p53 and inhibition of protein synthesis (11).…”
Section: Overview On Rna Oxidative Damages a Glimpse On Human Patholmentioning
confidence: 99%